KEBERLANJUTAN DAN TEKNOLOGI HIJAU DALAM PERSPEKTIF ISLAM - Atiyah Ulfah; Ani Cahyadi (CV. ADIBA AISHA AMIRA, 2025)
Behind the technological advancements and industrialisation in today's modern era, spur serious challenges that threaten the survival of life on earth, namely environmental issues. Climate change, pollution, and ecosystem damage are global issues that need to be addressed. The concept of sustainability and green technology in an Islamic perspective is increasingly relevant in maintaining the environmental ecosystem in maintaining environmental balance in an effort to meet the needs of the present generation without compromising the ability of future generations to meet their needs. The method used in this topic is through a qualitative approach by analysing related documents, such as scientific journals, and studies of Islamic perspectives and maqasid sharia perspectives and other experts. This research discusses the potential of green technology in supporting sustainable development in line with Islamic values. Green technology offers innovative solutions to address environmental problems such as climate change and environmental degradation. However, the implementation of green technology in Muslim-majority countries in reality still faces various challenges, including lack of awareness, limited infrastructure, and lack of supportive policies. This study will analyse the factors affecting green technology adoption in the Islamic world and provide policy recommendations to accelerate the transition to a green economy.